The Role of Parents in Learning Activities during the Corona Virus Disease of 2019 (Covid-19) Pandemic in Students Grade 1 Elementary School: Peran Orang Tua Dalam Kegiatan Pembelajaran di Masa Pandemi Corona Virus Disease Of 2019 (Covid-19) Siswa Kelas 1 SD - Putri Indah Khusnul Khotimah; Rifki Afandi (Academia Open, 2021)
This study discusses the role of people in learning activities during the pandemic. Researchers found problems with online learning, teachers have difficulty monitoring students during learning, so they need parents as substitutes for teachers while studying at home. To examine these problems, researchers used a qualitative phenomenological approach. Data collection techniques using interviews and observation. The research subjects are parents of grade 1 students. Based on the results of the study, it shows that parents have a role (1) to prepare learning facilities such as cellphones, Wifi, internet data packages. (2) Parents accompany when learning takes place, doing assignments, homework, and practicum. While the problems of online learning experienced by parents are: (1) parents are busy with homework, there are also parents who have to work. (2) The lack of explanation from the teacher because they only got assignments through the WA group. (3) Parents do not understand the material so they find it difficult to help students. (4) It is difficult for parents to increase learning motivation.